2020
DOI: 10.1101/2020.10.28.20217455
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anakinra To Prevent Respiratory Failure In COVID-19

Abstract: Introduction The management of pneumonia caused by SARS-CoV-2 should rely on early recognition of the risk for progression to severe respiratory failure (SRF) and its prevention. We investigated if early suPAR (soluble urokinase plasminogen activator receptor)-guided anakinra treatment could prevent COVID-19-assocated SRF. Methods In this open-label prospective trial, 130 patients admitted with SARS-CoV-2 pneumonia SARS-CoV-2 and suPAR levels ≥6 μg/l were assigned to subcutaneous anakinra 100mg once daily for … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…A significant association was not observed in a retrospective study of 57 treated patients (aHR 0.79, 95% CI 0.44 to 1.42), 27 while an association was observed in a prospective study of 130 patients (aHR 0.49, 95% CI 0.26 to 0.91). 28 A significant unadjusted association was also observed in a further study of 52 patients treated with anakinra (HR 0.30, 95% CI 0.12 to 0.71). 29 RRs were calculated from four studies totalling 424 participants.…”
Section: Resultsmentioning
confidence: 61%
“…A significant association was not observed in a retrospective study of 57 treated patients (aHR 0.79, 95% CI 0.44 to 1.42), 27 while an association was observed in a prospective study of 130 patients (aHR 0.49, 95% CI 0.26 to 0.91). 28 A significant unadjusted association was also observed in a further study of 52 patients treated with anakinra (HR 0.30, 95% CI 0.12 to 0.71). 29 RRs were calculated from four studies totalling 424 participants.…”
Section: Resultsmentioning
confidence: 61%
“…Also shown in Figure 1 are significantly elevated levels of tumor necrosis factor alpha (TNFα), IL-10 and urokinase plasminogen activator receptor (uPAR). Plasma uPAR is elevated in COVID-19 patients and levels positively correlate with poor outcomes (Kyriazopoulou et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…For example, high doses of anakinra reduces deaths as well as number of days in the hospital (Cauchois et al 2020, Cavalli et al 2020, Huet et al 2020). Anakinra has also been administered in less severe hospitalized patients and resulted in similar reduction in disease (Kyriazopoulou et al 2020). Since anakinra blocks the IL-1 Receptor, the efficacy of anakinra may be due to reducing IL-1α or IL-1β.…”
Section: Introductionmentioning
confidence: 99%
“…Repurposing FDA-approved drugs that inhibit inflammatory cytokines or GSDMD, the final mediator of both cytokine release and inflammatory death, are worth continuing to assess in controlled clinical trials. Although anti-IL-1β (canakinumab) did not meet its endpoint for efficacy in hospitalized hypoxic COVID-19 patients (Novartis press release, 11/06/2020), an unpublished manuscript of a randomized control trial of anakinra (IL-1RA) in patients with SARS-CoV-2 pneumonia showed a highly significant reduction in the development of severe respiratory failure and overall clinical severity ( 53 ). The possible efficacy of antagonizing IL-1 implicates GSDMD activation in severe COVID-19 disease since IL-1 secretion depends heavily on GSDMD pore formation.…”
Section: Discussionmentioning
confidence: 99%